Effect of Growth Restriction on Fetal Heart Rate Patterns in the Second Stage of Labor - Epplin, Kristina A.; Tuuli, Methodius G.; Odibo, Anthony O.; Roehl, Kimberly A.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2015)
Objective We aimed to estimate the effect of intrauterine growth restriction (IUGR) on electronic fetal monitoring (EFM) patterns in the second stage of labor.Study Design We performed a 5-year retrospective cohort study of consecutive singleton, nonanomalous, term gestations. We compared IUGR infants, those with a birth weight less than the 10th percentile, with non-IUGR infants, those greater than or equal to the 10th percentile. Our primary outcome was the EFM patterns in the 30 minutes before delivery. A secondary analysis was performed excluding infants with composite morbidity. Logistic regression was used to adjust for body mass index, race, nulliparity, induction, and protracted labor.Results Out of the 5,388 infants, 652 (12.1%) were IUGR. IUGR fetuses had less accelerations (29.0 vs. 35.9%, p < 0.01), even among apparently normal infants (29.0 vs. 36.4%, p < 0.01). IUGR fetuses had a higher risk of decelerations, and in all, IUGR accounted for 6% of late decelerations (attributable risk 0.06, 95% confidence interval 0.02–0.10). There was no significant association between IUGR and bradycardia or minimal variability.Conclusion Growth restriction at term confers an increased risk of late decelerations, even in the absence of neonatal morbidity. EFM patterns may require different interpretations based on a priori risk and clinical factors.
Keywords: fetal monitoring; fetal heart rate; growth restriction; IUGR